A palaeobiological window into the Lower Cretaceous Cupido Formation: Puerto México section, Nuevo Leon, Mexico - Torres de la Cruz, Felipe de Jesús; Chacón Baca, Elizabeth; Gómez Mancha, Yesica Edith; Cossío Torres, Tomás (2018)
Abstract: A rich geobiological record of Cretaceous biotic and abiotic interactions around the protoGulf of Mexico has been preserved in the massive Cupido carbonate platform, i.e., in a sedimentary sequence that represents a depositional period of approximately 15 Myr. This work documents lateral facies variation on a dip slope reef from a new outcrop in the upper part of the Cupido Formation in the state of Nuevo Leon, Mexico. The measured transect is correlated with a stratigraphic column logged in a nearby section. The preserved fossil biota represents marginal reef facies dominated by abundant rudist shells such as Douvillelia skeltoni, Toucasia sp., Offneria sp., and Amphitrocoelus sp. associated with relatively large colonial corals (with diameters up to 25 cm) like Stelidioseris sp. and to a lesser extent, with stromatoporoids. Benthic foraminifers (miliolids and textularids) with associated dasycladalean algae such as Salpingorella sp. and Terquemella spp. dominate the microfossiliferous content in wackestones to packstones. This facies is overlain by a thin (15-30 cm) stromatolite horizon at the upper end of the measured section. This locality represents a new paleobiological and taphonomic window into one of the most extensive carbonate platform system developed along the margin of the Gulf of Mexico during the Cretaceous.